2015
DOI: 10.1161/hypertensionaha.115.06004
|View full text |Cite
|
Sign up to set email alerts
|

Tenascin-C May Accelerate Cardiac Fibrosis by Activating Macrophages via the Integrin αVβ3/Nuclear Factor–κB/Interleukin-6 Axis

Abstract: Abstract--Tenascin-C (TN-C) is an extracellular matrix protein not detected in normal adult heart, but expressed in several heart diseases closely associated with inflammation. Accumulating data suggest that TN-C may play a significant role in progression of ventricular remodeling. In this study, we aimed to elucidate the role of TN-C in hypertensive cardiac fibrosis and underlying molecular mechanisms. Angiotensin II was administered to wild-type and TN-C knockout mice for 4 weeks. In wild-type mice, the trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
76
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(83 citation statements)
references
References 33 publications
4
76
1
2
Order By: Relevance
“…In two recent papers, macrophages and neutrophils have been shown to play an important role in cardiac fibrosis following Ang II infusion. In mice treated with Ang II, Tenascin-C was unregulated, accelerating macrophage migration and synthesis of proinflammatory and profibrotic cytokines in the myocardium, ultimately resulting in a significant fibrotic response [120]. Tenascin-C is a matricellular protein not detected in normal adult heart, but expressed in several heart diseases closely associated with inflammation.…”
Section: End Effectors Of the Fibrotic Processmentioning
confidence: 99%
See 1 more Smart Citation
“…In two recent papers, macrophages and neutrophils have been shown to play an important role in cardiac fibrosis following Ang II infusion. In mice treated with Ang II, Tenascin-C was unregulated, accelerating macrophage migration and synthesis of proinflammatory and profibrotic cytokines in the myocardium, ultimately resulting in a significant fibrotic response [120]. Tenascin-C is a matricellular protein not detected in normal adult heart, but expressed in several heart diseases closely associated with inflammation.…”
Section: End Effectors Of the Fibrotic Processmentioning
confidence: 99%
“…al. demonstrated that αvβ3 is the functional receptor in macrophages for Tenascin-C, mediating migration and the inflammatory response [120]. In another study, Friedrichs et.…”
Section: End Effectors Of the Fibrotic Processmentioning
confidence: 99%
“…TN-C expression is an independent predictor of mortality in patients with dilated cardiomyopathy [121] and serum TN-C levels are a potentially useful predictor of LV remodelling and prognosis after MI [122]. A number of preclinical murine studies have shown that TN-C knockout improves cardiac remodelling and fibrosis after MI [123] or Ang II infusion [124]. TN-C knockout mice also exhibit delayed recruitment of myofibroblasts after MI [125].…”
Section: Modified Ecm Componentsmentioning
confidence: 99%
“…Indeed, TN-C can directly stimulate CF migration and myofibroblast transdifferentiation [125]. In addition to direct effects, TN-C may have indirect effects on CF for example by inducing IL-6 production from macrophages with resultant increased collagen production by CF [124].…”
Section: Modified Ecm Componentsmentioning
confidence: 99%
“…In addition, loss of TNC attenuates inflammation following cardiac fibrosis. TNC interacts with integrins localized on the surface of the macrophage, upregulating IL-6, and FAK-Src through NF-κB and augmenting the inflammatory response [168]. …”
Section: Ecm-cell Interactions In the Injured Myocardiummentioning
confidence: 99%